Bibliometric review of 1992–2022 publications on acupuncture for cognitive impairment - Zhou, Runjin; Xiao, Lu; Xiao, Wei; Yi, Yanfei; Wen, Huanhuan; Wang, Hongda (Frontiers in Neurology, 2022)
Objective. To explore the development context, research hotspots and frontiers of acupuncture therapy for cognitive impairment from 1992 to 2022 by visualization analysis. Methods. Literatures about acupuncture therapy for cognitive impairment were retrieved from the Web of Science Core Collection (WoSCC) until March 1, 2022. Basic information was collected by Excel 2007, VOSviewer 1.6.17 was used to analyze co-occurrence of countries, institutes and authors. Co-citation maps of authors and references were analyzed by CiteSpace V.5.8.R3. In addition, CiteSpace was used to analyze keywords cluster and forecast research frontiers. Results. A total of 279 literatures were retrieved, including 19 countries, 334 research institutes and 101 academic journals. The most published country and institutes were the People's Republic of China (217) and Fujian University of Traditional Chinese Medicine (40). Ronald C Petersen owned the highest co-citations (56). Keywords and co-cited references cluster showed main research directions in this area, including “ischemic stroke”, “cerebral ischemia/reperfusion”, “mild cognitive impairment”, “Alzheimer's disease”, “vascular dementia”, “vascular cognitive impairment with no dementia”, “multi-infarct dementia”, “synaptic injury”, “functional MRI”, “glucose metabolism”, “NMDA”, “nuclear factor-kappa b pathway”, “neurotrophic factor”, “matrix metalloproteinase-2 (MMP-2)”, “tumor necrosis factor-alpha”, “Bax”, “Caspase-3”, “Noxa”. Trending keywords may indicate frontier topics, including “randomised controlled trial”, “rat model”, “meta-analysis”. Conclusion. This research provides valuable information for the study of acupuncture. Diseases focus on Mild Cognitive Impairment, Alzheimer's disease and Vascular Dementia. The mechanism of acupuncture in improving the disease mechanism involved microglia polarization state and neuroinflammation repair, regulating autophagy and apoptosis, and improving energy metabolism in the brain. The development of functional magnetic resonance imaging will better explain the therapeutic effect of acupuncture treatment.